Development and Validation of a Specific Stability Indicating High Performance Liquid Chromatographic Methods for Related Compounds and Assay of Solifenacin Succinate - B. V. Rami Reddy; B. Srinivasa Reddy; N. V. V. S. S. Raman; K. Subhash Reddy; C. Rambabu (Journal of Chemistry)
Gradient, reverse phase liquid chromatographic methods were developed separately for the related compounds and solifenacin succinate, an active pharmaceutical ingredient used for the treatment of overactive bladder. Gradient LC method was employed for related compounds. The mobile phase-A contains a 0.01 M phosphate buffer pH: 3.5±0.05 with orthophosphoric acid (88%) and mobile phase-B contains a mixture of acetonitrile and water in the ratio of 90 : 10(v/v). The flow rate was 1.0 mL/minute, column temperature was kept at 35°C, and detection was monitored at 220 nm. In the developed HPLC method the resolution between solifenacin succinate and its closely eluting impurity, that is, solifenacin N-oxide was found to be greater than 3.0. The drug was subjected to stress conditions such as hydrolysis, oxidation, photolysis, and thermal degradation. Considerable degradation was found to occur in only oxidative stress condition. Degradation product formed during oxidative stress condition was found to be impurity-C and it can be identified by LC-MS. The stress samples were assayed against a qualified reference standard and the mass balance was found close to 99.5%. The developed RP-LC method was validated as per ICH guidelines. We also developed LC-MS/MS method for determination and identification of these impurities in solifenacin succinate.